Pengaruh Penggunaan Jenis Coolant Jumbo, Megacools dan Hikari terhadap Efektivitas Pendinginan Mesin Nissan Livina 1800cc - Basir, Aang Abdul; Laksana, Alfian Hudan; Himawan, Citrakara Upendra S.K.; Prasetya, Yanto Budi; Pranata, Bintang (Universitas Borneo Tarakan, 2025)
This study aims to analyze the influence of using Jumbo, Megacools, and Hikari coolant types on the cooling effectiveness of Nissan Livina 1800cc engine. The research method used is experimental by testing the three types of coolant under the same engine operating conditions, comparing radiator effectiveness parameters based on differences in engine rotation time and RPM variations. Data collection was conducted systematically at standardized time intervals and engine rotations to obtain accurate and reliable results. The research findings indicate that Jumbo coolant type provides the highest cooling effectiveness compared to the other two coolant types. Based on the analysis of differences in engine rotation time, Jumbo coolant recorded radiator effectiveness of 0.234 at 30 seconds. The radiator effectiveness of Jumbo coolant also increased along with the increase in engine rotation, with the highest value of 0.246 recorded at 2200 RPM. Overall analysis shows that Jumbo coolant has the highest overall radiator effectiveness with an average value of 0.216. These findings indicate that the selection of coolant type significantly affects the performance of the engine cooling system, with Jumbo coolant as the optimal choice for improving cooling effectiveness in Nissan Livina 1800cc engines.